PENINGKATAN HASIL BELAJAR IPS MENGGUNAKAN STRATEGI PEMBELAJARAN AKTIF INFORMATION SEARCH PADA SISWA KELAS IV SD - Diana, Diana; Marli, Suhardi; Kresnady, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research to describe the increase in student learning activities using active learning  information retrieval strategy in the fourth grade public elementary School 07 east Pontianak.  The method that used in this research was descriptive method with a from of classroom action research. The subject in this research were teacher and 28 students of classroom IV. The procedure in this research consist of four step: planing, action, observation, and reflection. The data collection technique that used in this research were direct observation technique  and scrutiny documents. The data collection tehnique that used in this research were observation sheets and sheets of scrutiny documents. This research result: 1) the ability of teacher to plan learning in cycle 1, with avarage score of  3,61. In cycle 2 become 3,84. 2) the ability of teacher in implemanting the learning in first cycle, with an average score of 3,54, in cycle 2 to 3,69. 3) an increasein the avarage learning outcomes off class IV at first cycle is 69,64 the second cycle increase to 86,42.  Keywords : LearningOutcomes, Civics Learning, Aktif Information Search